Choosing a density functional for modeling adsorptive hydrogen storage: reference quantum mechanical calculations and a comparison of dispersion-corrected density functionals1. Issue 9 (7th March 2015) - Kocman, Mikuláš; Jurečka, Petr; Dubecký, Matúš; Otyepka, Michal; Cho, Yeonchoo; Kim, Kwang S.
<x xml:space="preserve">Abstract</x> Various dispersion-corrected density functionals are compared with high level QM data for several model complexes for adsorptive hydrogen storage.